ANALISIS KETERAMPILAN PRAKTIKUM MAHASISWA PGMI DALAM MENGGUNAKAN KIT IPA - Gusti Handayani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2019)
This study aims to analyze the practical skills of undergraduate of the Elementary Madrasah Teacher Education Study Program (PGMI) in using Science KITs in the Laboratory Management course. This study uses a qualitative approach with descriptive methods. The research sample consisted of 30 students. Data collection was carried out through observation and questionnaire distribution. Data were analyzed using descriptive analysis techniques through data reduction, data presentation, and conclusion drawing. The results of the study showed that based on the questionnaire, students' practical skills obtained a percentage of 72% and were in the good category. Meanwhile, based on the results of observations during the practical activities, students' skills obtained a percentage of 64% and were included in the sufficient category. The aspect that obtained the highest score, both based on the results of the questionnaire and observations, was the attitude aspect, which showed that students had good responsibility, discipline, and cooperation during the practicum. Thus, it can be concluded that the practical skills of PGMI undergraduates in using Science KITs have been in the good category, although there are still several aspects of technical skills that need to be improved through more intensive and continuous practical training so that students have optimal laboratory competencies as prospective elementary school teachers.